EVALUATION OF THE TOURISM POTENTIAL OF ERIN IJESHA (OLUMIRIN) WATERFALLS, OSUN STATE, NIGERIA - Arabomen, Oghenekevwe Joy; Babalola, Folaranmi Dapo (FUDMA Journal of Sciences, 2025)
Nature-based tourism is increasingly recognized as a tool for rural development when it generates income, jobs, and infrastructure while conserving ecosystems. In Nigeria, many iconic sites, including Olumirin Waterfalls, remain underdeveloped, with limited empirical evidence on their tourism potential. This study evaluated the tourism potential of Erin-Ijesha (Olumirin) Waterfalls using the adapted Tourism-Livelihood Interaction Model within the Socio-Ecological Systems Framework. The objectives were to examine perceived attractions, benefits, challenges, and negative impacts of tourism in the area. A mixed-methods approach was applied to 100 participants comprising tourists and residents. Requisite data were collected through structured questionnaire, in-depth interviews, and direct observations. Data analysis involved descriptive statistics, Pearson Chi-square tests and thematic analysis. The results showed that most tourists were male (56%), aged 21-40 years (66%), with tertiary education (52%). Natural scenery and the multiple waterfalls were the main attractions (78%), while recreation was also important (62%). Motivation differed significantly by age group (χ²=11.36, p<0.05), with younger visitors more likely to cite recreation and photography. Among residents, farming (36%) and trading (32%) were main occupations. While a few (n=6) saw no community benefit, most reported tourism created local jobs (56%) and boosted petty trading (49%), with benefits significantly linked to occupation type (χ²=8.17, p=0.017). Key challenges include poor road access (60%), inadequate facilities (60%), littering (46%), and vegetation disturbance (39%). Overall, Erin-Ijesha Waterfalls has high but underutilized tourism potential. Improving infrastructure, promoting community participation, and ensuring equitable benefit-sharing are critical to realizing its socio-economic and cultural value.